Gymnastic methodology of Professor García Fraguas - M.ª José DANIEL HUERTA (Ediciones Universidad de Salamanca, 2017)
This article shows the proposal didactic developed by teacher García Fraguas on gymnastics at the end of the nineteenth century. Based on this method we are going to explain the system used to keep order and discipline, the development of the lessons, the assessment system, the suitable clothing and hygienic rules, among others. The aim to improve the current conditions took him to visit schools and high schools and attend to different congresses related to physical education. The result of their experience was a news and original methodology. As for as the teaching learning of the gymnastic discipline, it should be remarked that criticized the methods of teaching used in most schools because he was sure that the lessons were boring, so they were not or profitable and enjoyable for students.